3D Assessment of Endodontic Lesions with a Low-Dose CBCT Protocol - Marco Portelli; Angela Militi; Antonino Lo Giudice; Roberto Lo Giudice; Lorenzo Rustico; Rosamaria Fastuca; Riccardo Nucera (MDPI AG, 2020)
Background: Cone beam computed tomography (CBCT) is often used in different fields of dental science, especially in complex anatomical districts like the endodontic one. The aim of this study is to propose a low-dose CBCT protocol useful in cases of endodontic lesions. Methods: The device used was a MyRay Hyperion X9-11x5; the low dose setting of the machine was 90 Kv, 27 mAs, CTDI/Vol 2.89 mGy. The absorbed organ doses have been evaluated with an anthropomorphic phantom loaded with thermoluminescent dosimeters positioned at the level of sensitive organs like brain, bone marrow, salivary glands, thyroid, esophagus, oral mucosa, extrathoracic airways, and lymph nodes. Equivalent and effective doses have been calculated; the last one has been calculated using the recommendations approved by the Main Commission of ICRP (International Commission Radiological Protection) in March 2007. For the assessment of image quality, five senior clinicians, independent and experienced clinicians, were asked to state if CBCT scans were accurate enough to assess endodontic lesions. Results: The use of a low-dose CBCT acquisition produced the lowest organ dose (5.01 microSv) at the level of the esophagus. Image quality has been considered accurate enough for endodontic diagnostic needs. Conclusions: CBCT low-dose protocol can be used over the standard one in endodontic special cases because it provides a significantly lower radiation dose to the patients while ensuring good image quality. However, further studies are necessary to evaluate the opportunity of low-dose CBCT exams in endodontic clinical practice.